Agronomic and physiological responses of potato subjected to soil compaction and/or drying. (2nd February 2021) - Huntenburg, Katharina; Dodd, Ian C.; Stalham, Mark
Abstract: Compact and dry soils impede root growth and restrict plant water availability, respectively, potentially causing leaf water deficit. Although both stresses likely co‐occur in the field and limit yield, little is known about their combined impact on plant growth and physiology over a whole season, especially in a tuberous crop like potato. Field‐grown potato ( Solanum tuberosum L. var. 'Maris Piper') was exposed to factorial combination of deficit irrigation (watering when soil moisture deficit reached 60 vs. 25 mm) and soil compaction (compacted with heavy machinery vs. uncompacted), with plant growth and leaf physiology measured weekly. Shoot growth was restricted by adverse soil conditions, while leaf water status, photosynthesis rates and leaf abscisic acid (ABA) levels did not vary significantly between treatments. Across all treatments, final yield was linearly correlated ( R 2 = 0.71) to mid‐season shoot biomass. Compared to well‐watered plants growing in loose soil, soil compaction, deficit irrigation and their combination decreased final tuber yield similarly, by 23%–34%. Surprisingly, tuber size distribution was more dependent on irrigation management than on soil strength. Plants exposed to deficit irrigation produced more, smaller potatoes than their respective control. Thus, low soil water availability and/or compact soil caused these field‐grown potatoes to restrict shoot growth rather than limit leaf gas exchange. Further research is needed to understand the role of hormonal signalling in regulating tuber growth when plants are exposed to compact and dry soils. Abstract : Compact and dry soils impede root growth and restrict plant water availability, respectively. Shoot growth of potato ( Solanum tuberosum L. var. 'Maris Piper') was restricted by adverse soil conditions, while leaf water status, photosynthesis rates and leaf ABA levels did not vary significantly between treatments. Across all treatments, final yield was linearly correlated ( R 2 = 0.71) to mid‐season shoot biomass. Thus, low soil water availability and/or compact soil caused these field‐grown potatoes to restrict shoot growth rather than limit leaf gas exchange.